UPAYA PENINGKATAN PEMBELAJARAN LARI CEPAT MELALUI GAWANG AMAN DI SD 137957 KOTA TANJUNG BALAI KELAS V - Nurhasanah, Nurhasanah (Jurnal Sabilarrasyad, 2021)
This study aims to determine all parties who are safe and able to improve learning sprinting in grade v SD Negeri 137957 Kota Tanjung Balai. This type of research uses PTK. The research location was at SD Negeri 137957 Kota Tanjungbalai. The results showed that in this cycle 1, obstacles were still found that made learning less than optimal, namely, there were still some students who were not happy with the group division that the teacher was doing. The obstacles that appeared in meeting 1 were directly completed by the researcher in meeting 2, by explaining to each student. In 2 fast running movements, the fifth-grade students are getting better, this can prove that when evaluating the direction and ranking process quickly, without losing balance and increasing running speed, and doing the transition to running movements well. But there are still 5 students who have not completed the fast running movement. In cycle 3, the fast running movement of class V sis is getting better, this can be proven by the evaluation of sprinting which reaches 100% at the end of the cycle. In addition, the time reached by students also increased from cycle 2.